Mood and Cerebral Perfusion Revisited - Klaus P. Ebmeier (Behavioural Neurology)
Twenty patients with major depression and observed diurnal variations of mood were examined using clinical and neuropsychological measures and perfusion HMPAO-SPECT at 8 a.m. and 8 p.m. In thirteen patients depression scores varied more than 15% although 4 patients with reverse diurnal variation caused mean group depression scores to be not different between morning and evening. There was an overall trend for higher depression scores to be associated with higher perfusion in posterior cingulate. This was mainly accounted for by significant positive correlations in the morning scan in posterior, but also anterior cingulate and medial prefrontal cortex compared with evening scans. This means that morning regression slopes were steeper than evening slopes. This result is discussed with regard to possible interpretations, such as adaptive or habituating changes during the day that may occur in depressed patients.